Treatment of Retinoblastoma: What Is the Latest and What Is the Future - Schaiquevich, Paula; Francis, Jasmine H.; Cancela, María Belén; Carcaboso, Angel Montero; Chantada, Guillermo L.; Abramson, David H. (Frontiers in Oncology, 2022)
The management of retinoblastoma, the most common intraocular malignancy in children, has changed drastically over the last decade. Landmark developments in local drug delivery, including safer techniques for intravitreal chemotherapy injection and ophthalmic artery chemosurgery, have resulted in eye globe salvages that were not previously attainable using systemic chemotherapy or external beam irradiation. Novel drugs, oncolytic viruses, and immunotherapy are promising approaches in the treatment of intraocular retinoblastoma. Importantly, emerging studies of the pattern of tumor dissemination and local drug delivery may provide the first steps toward new treatments for metastatic disease. Here, we review recent advances in retinoblastoma treatment, especially with regard to local drug delivery, that have enabled successful conservative management of intraocular retinoblastoma. We also review emerging data from preclinical and clinical studies on innovative approaches that promise to lead to further improvement in outcomes, including the mechanisms and potential uses of new and repurposed drugs and non-chemotherapy treatments, and discuss future directions for therapeutic development.